2020
DOI: 10.1177/1535370220947387
|View full text |Cite
|
Sign up to set email alerts
|

Calliandra portoricensisameliorates ovarian and uterine oxido-inflammatory responses inN-methyl-N-nitrosourea and benzo[a]pyrene-treated rats

Abstract: Reproductive dysfunction stemming from chemical agents may lead to infertility. We examined the protective effects of Calliandra portoricensis ( CP) extract on benzo[a]pyrene (BaP) and N-methyl- N-nitrosourea (NMU)-induced ovarian and uterine toxicity in rat, treated as follows: control (group 1), NMU + BaP (group 2), groups 3 and 4 received (NMU + BaP), and CP (50 and 100 mg/kg), respectively. Group 5: CP (100 mg/kg) alone, group 6: (NMU + BaP) and vincristine (VIN: 0.5 mg/kg) and group 7: VIN alone. Rats wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…The total proteins of the liver and kidney tissues were estimated following an established protocol 52 to determine the exact concentration of any protein of interest in the tissue. The markers of oxidative and nitrosative stress in the liver and kidney of rats were determined following well-documented protocols: Superoxide dismutase (SOD) activity 53 , 54 ; catalase (CAT) activity 55 , 56 using H 2 O 2 as a substrate; glutathione S-transferase (GST) activity 57 ; glutathione peroxidase (GPx) activity 58 , 59 ; reduced glutathione (GSH) level 60 , 61 . Also, total sulfhydryl (TSH) level 62 , 63 ; xanthine oxidase (XO) activity 63 , 64 ; myeloperoxidase (MPO) activity 18 , 65 ; nitric oxide (NO) level 48 , 66 were also evaluated accordingly.…”
Section: Methodsmentioning
confidence: 99%
“…The total proteins of the liver and kidney tissues were estimated following an established protocol 52 to determine the exact concentration of any protein of interest in the tissue. The markers of oxidative and nitrosative stress in the liver and kidney of rats were determined following well-documented protocols: Superoxide dismutase (SOD) activity 53 , 54 ; catalase (CAT) activity 55 , 56 using H 2 O 2 as a substrate; glutathione S-transferase (GST) activity 57 ; glutathione peroxidase (GPx) activity 58 , 59 ; reduced glutathione (GSH) level 60 , 61 . Also, total sulfhydryl (TSH) level 62 , 63 ; xanthine oxidase (XO) activity 63 , 64 ; myeloperoxidase (MPO) activity 18 , 65 ; nitric oxide (NO) level 48 , 66 were also evaluated accordingly.…”
Section: Methodsmentioning
confidence: 99%
“…Portion of the previously prepared supernatant from the right testis and epididymis was used for the evaluation of oxidative stress in the testis and epididymis. SOD activity was measured by the previously reported method of Misra and Fridovich (1972), Adefisan et al (2020); CAT activity according to the method of Clairborne (1995), Owumi, Nwozo, Effiong, et al (2020). As previously reported, total sulfhydryl group and reduced GSH was assessed by Ellman’s (1959), Arowoogun et al (2020) and Jollow et al (1974), Owumi et al (2019) method respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The supernatant was after that used for the oxidative stress assays. SOD activity was determined by the method described by Misra and Fridovich and as previously reported (Adefisan et al., 2020; Misra & Fridovich, 1972); CAT activity was determined using H 2 O 2 as a substrate according to the process of Clairborne and as previously reported (Clairborne, 1995; Owumi, Nwozo, et al, 2020); protein concentration was determined by the method of Lowry et al, and as previously reported (Lowry et al., 1951); total sulfhydryl group was determined by the process of Ellman (Arowoogun et al., 2021; Ellman, 1959); reduced GSH was determined using the method described by Jollow et al, and as previously reported (Jollow et al., 1974; Owumi, Aliyu‐Banjo et al, 2019); GST was assayed (monitored at 340 nm) using Habig’s method (Habig et al., 1974); GPx activity was determined according to the process of Rotruck et al, and as previously reported (Owumi, Danso, et al, 2020; Rotruck et al., 1973); xanthine oxidase was quantified by the method of Bergmeyer et al and reported recently (Buege & Aust, 1978; Owumi, Elebiyo, et al, 2020) and Lipid peroxidation marker was quantified as malondialdehyde (MDA) according to the method described by Ohkawa and as previously reported (Folayan et al., 2020; Ohkawa et al, 1979) and expressed as μmol MDA/mg protein.…”
Section: Methodsmentioning
confidence: 99%